Interactive Effects of Carbon Dioxide Molecules, Demographic Changes on Financial Development in Sub-Saharan Africa - Manasseh, Charles O.; Logan, Chine Sp; Igwemeka, Ebele C.; Ekwunife, Faith C.; Onoh, Chukwunonso F.; Okanya, Ogochukwu C.; Eje, Grace C.; Ezechi, Kingsley C.; Okonkwo, Wilfred O. (International Journal of Energy Economics and Policy, 2024)
This study examines the interaction impacts of carbon dioxide molecule emissions and population changes on financial development in Sub-Saharan Africa (SSA). The study used yearly time series data spanning the years 2000 to 2021. Following the PMG and FE results, the dynamic system GMM estimator was used in the study. The study found a significant inverse long-run relationship between carbon dioxide (CO2) emissions and financial development. Also, demographic changes have a significant positive impact on financial development. The interaction term findings demonstrate that changes in CO2 and GHG emissions have a negative and significant influence on the impact of the money supply ratio on financial development in SSA. The study suggests policies that support the adoption of financial aid or other incentives for initiatives that reduce CO2 emissions. Additionally, initiatives to support financial inclusion, uphold financial stability, encourage the expansion of infrastructure, advance social welfare, and ensure environmental sustainability should be made. Therefore, the SSA countries might benefit from their expanding populations to drive long-term economic expansion and improve living standards for their people.